Observation of Υ(4S) Decays to π+π-Υ(1S) and π+π-Υ(2S) - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2006)
We present the first measurement of Υ(4S) decays to π+π-Υ(1S) and π+π-Υ(2S) based on a sample of 230×106Υ(4S) mesons collected with the BABAR detector. We measure the product branching fractions B(Υ(4S)→π+π-Υ(1S)) ×B(Υ(1S)→μ+μ-)=(2.23±0.25stat±0.27syst) ×10-6 and B(Υ(4S)→π+π-Υ(2S))×B(Υ(2S) →μ+μ-)=(1.69±0.26stat±0.20syst)×10-6, from which we derive the partial widths Γ(Υ(4S)→π+π-Υ(1S))=(1. 8±0.4)keV and Γ(Υ(4S)→π+π-Υ(2S))=(2. 7±0.8)keV. © 2006 The American Physical Society.